Peran Baitul Mal pada Era Nabi Muhammad dalam Pengelolaan Fiskal dan tatanan Sosial Ekonomi - , Miftahurrahmah; Hidayat, Faisal (Bertuah Jurnal Syariah dan Ekonomi Islam, 2024)
This paper investigates the involvement of Baitul Mal in fiscal and socio-economic administration during the time of Prophet Muhammad and its significance in relation to modern Islamic economics. The study utilizes a qualitative research methodology with a historical perspective, incorporating a literature review, descriptive analysis, and contextualization of historical data. The results suggest that Baitul Mal, with its effective organization and operating methods, efficiently gathered and distributed several forms of wealth, including zakat, sadaqah, ghanimah, fai, and kharaj, in a just and transparent manner. Baitul Mal's main responsibilities encompass the administration of zakat to mitigate economic inequality, the distribution of ghanimah and fai for the betterment of the public, and the allocation of kharaj for the construction of infrastructure. The implementation of fiscal policies through Baitul Mal has proven to be effective in decreasing poverty and improving social welfare. The enduring significance of the ideals of fairness, transparency, and efficiency, which were upheld during the era of Prophet Muhammad, suggests their potential applicability in contemporary economic systems. Therefore, this work provides a substantial contribution to comprehending the significance of Baitul Mal in the context of Islamic economics and provides essential direction for formulating comprehensive and enduring Islamic economic policies in the contemporary period.